Peranan Sistem dan Teknologi Pada Proses Bisnis Organisasi - Pratama, Rian Dandi; Nasution, Muhammad Irwan Padli (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2024)
This article describes the role of information in a company as the blood that flows in the human body. Therefore, management information systems are very important to collect, analyze and present data in real-time using technology. The research method used is a quantitative causality method with library materials as data sources (Library research). The research results show that it is easier for companies to integrate business data with management information systems, improve information quality, provide management control, and speed up business data analysis. This allows management to focus more on strategic, creative and innovative aspects to improve the quality of the company's products and services, as well as shorten the production or service process cycle thereby increasing competitiveness.